An antenna group delay measurement method based on three‐antenna extrapolation and least residual error curve fitting technique. Issue 7 (7th May 2018) - Lin, Haoyu; Song, Zhenfei; Wang, Xuetian; Gao, Hongmin
Abstract: This article presents an antenna group delay (GD) measurement method based on the three‐antenna extrapolation technique and a least residual error curve fitting. The system GD is measured as a function of distances in an extrapolation range; then the antenna GD is determined together with antenna scattering characteristic (SC) defined by Kerns using GD variation curve fitting according to the measurement model and measured data. Measurement in frequency band of (1575.42 ± 16) MHz for a standard gain horn antenna is given, and the results of the antenna GD and SC at 1575.42 MHz are 2.83 ns and 0.36, respectively. The GD measurement results are with good agreement with our previously developed method, within a difference of 0.05 ns in the whole frequency band, and thus proposed method is cross‐checked. Although the proposed method is a little complicated and time consuming, its unique advantages are still prominent, as the optimization is a general solution for eliminating antenna multiple reflection; and the method can determine the two parameters of antenna GD and SC simultaneously.